The Role of Consumer Dispute Settlement Board in Providing Legal Protection in Makassar City - Makkasau, Andi Kasman; Pattenreng, Andi Muh. Arfah; Hamid, Abd. Haris (Postgraduate Bosowa University Publishing, 2018)
This study aimed at determining the implementation of duties and authority of Consumer Dispute Settlement Agency (BPSK) Makassar in the supervision of inclusion of standard clauses and settlement of disputes between consumers and business actors in Makassar. This research was conducted in Makassar at BPSK Office in Makassar. The method used was the empirical normative approach. The purpose of this approach was to analyze the extent to which law or regulation is effective in the community regarding the role of the Consumer Dispute Settlement Agency in providing legal protection for consumers in Makassar. The results of this study indicated that the implementation of supervision of raw clauses by BPSK Makassar was effective, BPSK Makassar only limited to the supervision after the complaints of consumers. The implementation of consumer dispute resolution by BPSK Makassar applies the conciliation, mediation, and arbitration. Based on the data obtained from 2010-2015, every year the number of cases received and resolved by BPSK Makassar is increased approximately 179 cases as alleged violations complained to BPSK Makassar.